Network security : a decision and game-theoretic approach - Alpcan, Tansu , 1975-; Basar, Tamer (Cambridge University Press, 2010)
"Network security is an important, challenging, and multi-dimensional research field.In its study, theory and practice should function together as parts of a feedback loop.Game, optimization, and control theories, among others, provide a mathematical foundation to formalize the multitude of decision-making processes in network security. The analytical approaches and quantitative frameworks presented lead to better allocation of limited resources and result in more informed responses to security problems in complex networked systems and organizations"-- Provided by publisher